INSTAGRAM CAPTION AS ONLINE LEARNING MEDIA ON THE SUBJECT OF EXTENDED WRITING DURING PANDEMIC OF COVID-19 - Bestari, Ade Christanty Yudha; Faiza, Dinar; Mayekti, Meilina Haris (Surakarta English and Literature Journal, 2020)
This journal contains Instagram caption as online learning media on the extended writing subject in the midst of Covid-19 pandemic. Instagram is one of the popular culture products in the digital era. It is one of choices to be online learning media especially in improving writing. Most people have Instagram account in the recent time. They are very active in using Instagram. Anything can be viral on this platform. This study presents the students’ perceptions of using social media Instagram. The data were analyzed by using qualitative standard of research. The result of this research is there are the advantages in using of Instagram caption as online learning media on the subject of extended during pandemic of Covid-19. The first advantage shows that participants can understand grammatical English like understanding on simple past tenses, subject- verb agreement and spelling correctly. The second, the participants can build their confidence in English writing by writing some Instagram captions. The third, the participants do writing as a daily habit. They are stimulated to write English captions in the lockdown time. The fourth, the participants got improving vocabularies.